QUALIDADE DE VIDA DE CUIDADORES DE IDOSOS VINCULADOS A UM PROGRAMA DE ATENÇÃO DOMICILIAR. - Melo da Costa, Francine; Tadei Nakata, Priscila; Raymundo Brocker, Anemarie; Girardi Paskulin, Lisiane Manganelli; Pinheiro de Morais, Eliane (Journal of Nursing UFPE / Revista de Enfermagem UFPE, 2016)
Objective: to verify whether the monitoring in a home care program has changed the quality of life (QOL) and the burden of caregivers of elderly people. Method: intervention study comparing the QOL scores and burden of 21 caregivers of elderly patients before and four months after their inclusion in a home care program, from July 2008 to January 2011. The data were analyzed in the Statistical Package for Social Sciences (SPSS) 18.0 program and the significance level adopted was 5% (p < 0.05). Results: the better the perception of QOL in the domains psychologic and environment, the lower the assessed burden of the caregiver. Statistically significant changes were not identified in the overload and in the QOL at the time of entry in the program and four months later. Conclusions: this study expands the understanding of nurses about caregivers vulnerabilities and identifies the need to increase home care to them and to the elderly.